General aspects of concurrent aerobic and strength training for performance in team sports - Robineau, J. (Concurrent aerobic and strength training. Scientific basics and practical applications, 2019)
Concurrent strength and aerobic training is regularly utilized in team sports in an attempt to improve the ability to repeat high-intensity efforts. Current evidence suggests that this approach may in some circumstances attenuate gains in muscle mass, strength, and power, collectively known as the interference effect. The main aim for practitioners, therefore, is to reduce possible negative effects of combined aerobic and strength training in order to optimize neuromuscular and cardiorespiratory adaptations by manipulating training variables such as order and recovery time between sequences, type, and modality of training. This chapter will provide methodological considerations for team sports such as rugby and water polo. Abstract from author